Perilaku Cyberbullying Dengan Media Instagram Pada Remaja Di Yogyakarta - Fitransyah, Retha Rizky; Waliyanti, Ema (IJNP (Indonesian Journal of Nursing Practices), 2018)
Adolescents cyberbullying behavior on social media has become one of unresolved problems. Factors that influence adolescents in cyberbullying includes high use of social media, low empathy, and experience of being bully victims. This situation can give a negative impact to victims psychological. This research use a qualitative method of the phenomenology approach. The data retrieval is done by deep interviews and observations through the social media Instagram informants. The informant in this research amount 5 students consisting of senior high school and junior high school in Yogyakarta determined by purposive sampling. The validity of data is done by using triangulation methods and peer debriefing. The data analysis researchers using open code software 4.03.        The results of research through observation on social media Instagram showed the types of cyberbullying carried out by adolescents in Yogyakarta such as : 1). Make rude comments, 2). Update instastory, 3).Upload photos, and 4). Comment on photos. In addition, the results of the research through deep interviews showed that the behavior of adolescent cyberbullying was influenced by several factors such as 1). The intensity of social media use, 2). The ability of empathetic actors, and 3). Character of the victim. Cyberbullying behavior in adolescents such as uploading photos, rude comments, updating instastories, and commenting on photos by using harsh words has a negative impact on both perpetrators and victims so they need more attention from schools and parents. Based on the results of the research, it can be suggested for the future researchers to be able to intervene through health promotion on social media related to cyberbullying behavior so that there is no increase in cyberbullying on social media besides that parents can build effective communication and provide moral support so that teens avoid cyberbullying behavior.